The challenge of adopting sexual orientation resolutions at the UN Human Rights Council - JORDAAN, Eduard (Institutional Knowledge at Singapore Management University, 2016)
Since the mid-1990s, UN special procedures reports have increasingly addressed human rights violations related to sexual orientation. However, it was not until 2011 that the first UN resolution on human rights and sexual orientation was adopted. After considerable difficulty, a follow-up resolution was adopted in late 2014. This policy and practice note examines the challenges of adopting sexual orientation resolutions at the UN Human Rights Council. The discussion is organized around six challenges: the need for Southern leadership, the strong counter-reaction that sexual orientation and gender identity (SOGI) issues generate at the UN, finding a strong leader, divisions within civil society, securing the necessary votes, and the contents of the resolution. The paper concludes with a reflection on the practical and strategic implications of these challenges.